Ulotka z pizzerii – zwięzły przekaz do klienta - Maciej Kośmicki, Maciej Kośmicki (Człowiek i Społeczeństwo, 2019)
The article presents the phenomenon of pizza as the most popular, especially is bigger cities, fastfood meal which, as a coincidence (approval by Italian elites in the mid-19th century and economic emigrants after World War II), has gradually gained cosmopolitan and popcultural recognition. The empirical project discussed in the paper is based on a qualitative analysis of flyers from pizza restaurants in Poznań. The flyers have turned out to be quite conventional in their form of advertisement as they mostly present pizza from the table or bird’s-eye perspective and avoid human representation. Additionally, while collecting research data, information on diverse models of running such eating places in big cities has been obtained, including: lack of a constant menu or possibility to order pizza by phone and pick it up by a client.